PROGRAM “ROLASAN” SEBAGAI MANAJEMEN PENINGKATAN KUALITAS HAFALAN AL-QUR’AN PADA SANTRI HAFIZAT PONDOK PESANTREN BAITUL AKBAR - Hanifah Hikmawati; Choiriyah, Umi (Inisiasi : Jurnal Manajemen Pendidikan Islam, 2024)
The quality of memorization is the level of goodness and badness of a person when memorizing the Qur’an. To achieve good quality memorization of the Qur'an, good management is needed to manage planning, organizing, implementing and supervising in order to achieve the goals set. The aim of this research is to find out: 1) Find out about the rolasan program at Pondok Pesantren Baitul Akbar Islamic, 2) Find out the quality of memorization for Hafizat santri at Pondok Pesantren Baitul Akbar, 3) Analyze the management of the rolasan program in improving the quality of memorization for Hafizat santri at Pondok Pesantren Baitul Akbar. This research uses a qualitative approach with descriptive methods. The data in this qualitative research is in the form of primary and secondary data obtained by interviews, observation and documentation. The data that has been collected is then analyzed using descriptive qualitative analysis methods. The results of this research are 1) The roll-out program at the Pondok Pesantren Baitul Akbar is carried out by planning, organizing, implementing and supervising. 2) The quality of santri memorization of the Qur'an at the Pondok Pesantren Baitul Akbar is getting maximum because the Islamic boarding school prioritizes murojaah rather than adding to memorization, 3) The management of the rolasan program can improve the quality of santri memorization, namely by memorizing the Qur'an listen to each other and pay attention to an assembly taking turns reading the juz while listening without recitation by the friend. Keywords: Management, Pondok Pesantren, Rolasan